If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + -10 = 0 Reorder the terms: -10 + 3c = 0 Solving -10 + 3c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 3c = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 3c = 0 + 10 3c = 0 + 10 Combine like terms: 0 + 10 = 10 3c = 10 Divide each side by '3'. c = 3.333333333 Simplifying c = 3.333333333
| (2x-1)+1=8 | | 13d+8=8d+53 | | x(4x+12)=-9 | | 3a+5b=26 | | 3r+38= | | 4x-10=-(9x+18) | | 4x^2+36y^2-72y-108=0 | | 17-10x=5x+65 | | 2x(x+3)=9 | | y^3-4y^2=0 | | 3(-2-x)=18 | | 7/8*6/5 | | 9m+24= | | 1/2w+7=2w-2 | | 27x-4=9x+2 | | x(x)-5+2forx=6 | | 2-4r=-14 | | 64x^3-49x=0 | | 2n=2n-1 | | 3t+2+2t=-53 | | x(x)-5+12= | | 5x^3+3x^2=125x+75 | | 8/11-2x=-2x+6/11 | | 5x^3/4+2=42 | | 29-5g+3=-3g+6g | | y+2=10 | | 32x-1/5=4 | | 3x-1/5=20 | | .2n-.594=3.5n+9.0 | | -.389y-.974=6.789y | | -3(2x-3)+15=9 | | 5(2x-6)=3(x+4) |